2009
DOI: 10.2105/ajph.2008.150367
|View full text |Cite
|
Sign up to set email alerts
|

Novice Drivers' Risky Driving Behavior, Risk Perception, and Crash Risk: Findings From the DRIVE Study

Abstract: The overrepresentation of youths in crashes involving casualties is a significant public health issue. Risky driving behavior is strongly linked to crash risk among young drivers and overrides the importance of risk perceptions. Systemwide intervention, including licensing reform, is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
1
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(140 citation statements)
references
References 43 publications
8
119
1
12
Order By: Relevance
“…Furthermore, if this trend continues, they would definitely also have long-term consequences for victims. These results are consistent with the findings of Ivers, Senserrick, Boufous and Stevenson (2009). Their results showed that younger drivers are associated with risky driving, high-levels of speed and have increased risks of crashing.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, if this trend continues, they would definitely also have long-term consequences for victims. These results are consistent with the findings of Ivers, Senserrick, Boufous and Stevenson (2009). Their results showed that younger drivers are associated with risky driving, high-levels of speed and have increased risks of crashing.…”
Section: Discussionsupporting
confidence: 92%
“…29 Another study from Australia revealed that poorer perception of safety was associated with an increased crash risk. 17 According to the available literature, effective interventions to reduce risky driving behaviours among teenagers and young people include the implementation of educational programmes to effectively change behaviours and help risky drivers to temper positive emotions related to driving and more fully understand the associated risks. 10,15 These interventions are in addition to more general measures targeting drivers, altering vehicle design and making the environment safer for road users.…”
Section: Discussionmentioning
confidence: 99%
“…Questions were developed by reviewing the relevant literature. 10,[17][18][19] A total of 21 items covering different risk-taking behaviours formed the main questionnaire. For each item, participants indicated on a 5-point scale how frequently they usually engaged in the behaviour when driving (1 = never, 2 = rarely, 3 = sometimes, 4 = frequently and 5 = always), their perception of the risk associated with the behaviour (1 = not risky at all, 2 = slightly risky, 3 = fairly risky, 4 = very risky and 5 = extremely risky) and their enjoyment of the behaviour (1 = strongly dislike, 2 = dislike slightly, 3 = neutral, 4 = like slightly and 5 = strongly like).…”
Section: Methodsmentioning
confidence: 99%
“…Usar el móvil mientras se conduce, conducir con sueño o cansancio, conducir por encima de la velocidad autorizada y distraerse al volante fueron las circunstancias con mayores frecuencias de implicación entre nuestros conductores. Este hecho ya ha sido documentado por la literatura en conductores jóvenes de otros países 3,32,33 . Así, un reciente estudio realizado en jóvenes conductores australianos detectó que, entre los principales comportamientos de riesgo al volante se encontraban: el exceso de velocidad, el uso del móvil, conducir cansado, llevar pasajeros sin cinturón, conducir solo, conducir de noche, bajo meteorología adversa y conducir bajo los efectos del alcohol u otras drogas 16 .…”
Section: Variables/categoríasunclassified
“…No en vano, representan la primera causa de mortalidad en todo el mundo entre los 15 a los 29 años, en especial entre los varones 1 . A ello han contribuido, entre otros factores, el exceso de velocidad, la conducción bajo los efectos del alcohol, la bús-queda de nuevas sensaciones o la escasa percepción de riesgo, tradicionalmente atribuidos a los jóvenes conductores 2,3,4 .…”
Section: Introductionunclassified